Rhodomollosides A and B, glycosides of methyl everninate from the aerial parts of Rhododendron molle - Yang, Xue-Rong; Tanaka, Naonobu; Song, Jing-Ru; Lu, Feng-Lai; Yan, Xiao-Jie; Li, Jian-Xing; Zhao, Xue-Ying; Kashiwada, Yoshiki; Li, Dian-Peng (Journal of asian natural products research, 2022)
Two new glycosides of methyl everninate, rhodomollosides A (1) and B (2), were isolated from the aerial parts of a medicinal plant Rhododendron molle. The structures of 1 and 2 were elucidated on the basis of detailed spectroscopic analyses as well as HPLC analyses for thiazolidine derivatives of their sugar moieties. The sugar moiety of rhodomolloside A (1) was elucidated to be a rare monosaccharide, D-allose, while rhodomolloside B (2) was assigned as a D-glucoside of methyl everninate. Furthermore, they were evaluated for their cytotoxicity against RAW264.7 cells, and for their inhibitory effects with a lipopolysaccharide (LPS)-stimulated murine macrophages RAW 264.7 cells model.